Theory and best practices in science communication training - Newman, Todd P. (Abingdon, Oxon, [England] Routledge, an imprint of the Taylor & Francis Group, 2020)
"This edited volume translates the growing body of research in science communication, education and journalism to inform best practices in science communication training programs around the world. Theory and Best Practices in Science Communication Training provides crucial empirical evidence about what works and what doesn't in science communication training. It analyses existing research around how scientists and science communication trainers view communication training and provides an in-depth overview of the various training exercises and activities that exist to aid scientists communicate with different audiences. It also provides an overview of assessment techniques and methods of evaluation, ranging from tools to measure self-reported intentions and behavior, to frameworks for measuring communication effectiveness across different mediums. With contributions from a diverse range of experts, this book will be of great interest to students, scholars and professional within this emerging field"--Provided by publisher.
"Earthscan from Routledge."
Includes bibliographical references and index.
Keywords: Communication in science -- Study and teaching